EFFECTS OF LOUVERS SHADING DEVICES ON VISUAL COMFORT AND ENERGY DEMAND OF AN OFFICE BUILDING. A CASE OF STUDY - Fernández-Hernández, Francisco Ángel; Cejudo-López, José Manuel; Peña Suárez, José Miguel; González Murriano, Mª Carmen; Carrillo Rueda, Simón (My University, 2017)
This paper evaluates the building energy demand and visual comfort of a real case with a glazed façade office building placed in Málaga (Mediterranean city in the south of Spain). South oriented facades receive such a high solar gain that cooling demand cannot be handled by the current HVAC system. As an environmental friendly solution, a shading control strategy based on vertical and horizontal louvers is proposed. The study consists of a comparison between the actual and the refurbished building with shading devices. Daylighting simulation is done with Daysim (Daysim, 2016). A group of offices with south, east and north oriented facades is chosen for the study. Horizontal louvers in the south façade and vertical louvers in the east facade are modelled and simulated. The simulation changes the angle of the louver: 0º (perpendicular to the glazing), -30º, 30º, -60º, 60º. Visual comfort parameters analyzed are: illuminance, daylight autonomy (DA) and useful daylight index (UDI). With respect to the thermal comfort, not only louvers orientation try to provide solar protection for glazed areas in cooling period but also maximize solar gains in heating period. However, an excessive daylight could affect discomfort glare. Shading control strategy must provide the equilibrium between both aspects. Thermal demand is calculated with Trnsys (TRNSYS, 2016).
Keywords: Arquitectura española; Daylight; Visual comfort; Control shading; Energy demand